2017
DOI: 10.5194/tc-2017-208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melting and fragmentation laws from the evolution of two large southern ocean icebergs

Abstract: Abstract. The evolution of the thickness and area of two large southern ocean icebergs, having drifted in open water for more than a year, is estimated through the combined analysis of altimeter data and visible satellite images. Most of the iceberg modelling studies uses two main melting formulations that are compared with the observed thickness evolution of our two icebergs, to test their validity in case of large icebergs. The first formulation, based on a fluid dynamics approach, would tend to underestimat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The finding that the size‐frequency distributions of PIIs were best represented by a power law model can similarly inform future predictions of the size‐frequency distributions of ice islands, which may be of particular interest to offshore industry concerned with these marine hazards. The mean slope of the power law distributions that were fit to the temporal and spatial snapshots in our study is very close to that reported for the size‐frequency distribution of Antarctic ice islands (−1.5; Bouhier et al, ; Tournadre et al, ). This suggests that ice islands in both the Arctic and the Antarctic deteriorate through a complex set of fracture and fragmentation mechanisms and that these deterioration processes occur similarly across a range of ice island sizes (Kirkham et al, ; Tournadre et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding that the size‐frequency distributions of PIIs were best represented by a power law model can similarly inform future predictions of the size‐frequency distributions of ice islands, which may be of particular interest to offshore industry concerned with these marine hazards. The mean slope of the power law distributions that were fit to the temporal and spatial snapshots in our study is very close to that reported for the size‐frequency distribution of Antarctic ice islands (−1.5; Bouhier et al, ; Tournadre et al, ). This suggests that ice islands in both the Arctic and the Antarctic deteriorate through a complex set of fracture and fragmentation mechanisms and that these deterioration processes occur similarly across a range of ice island sizes (Kirkham et al, ; Tournadre et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…The mean value associated with the drift of “PII‐A” from the 2010 calving event (0.067 m/s), as modeled by the CIS, was assigned to Δ u . The parameterization of Δ u is a potential source of uncertainty for the M b calculations within the thinning model (Bouhier et al, ; Jansen et al, ). A sensitivity analysis using the 2008 calving event was conducted to illustrate the effect of varying the assigned value of Δ u ; the assigned value of Δ u was adjusted by 1σ (+0.047 m/s) to show the resulting variation in the magnitude of meltwater input dispersed through the study region following the 2008 Petermann Glacier calving event.…”
Section: Methodsmentioning
confidence: 99%
“…Halliday et al (2012) calculated an average basal ablation rate of 3.4 cm d -1 from spot ice thickness and surface ablation measurements collected from PII-A on two dates over the summer of 2011. Studies conducted on Antarctic ice islands report basal ablation magnitudes estimated from remotely sensed altimetry data and modeled surface ablation (Jansen et al, 2007;Bouhier et al, 2017). Due to the lack of field observations of ice island thinning and ablation, the calibration and validation of ice island basal ablation models has previously relied upon such estimated basal ablation rates and modeled oceanographic data.…”
Section: Thinning Through Surface and Basal Ablationmentioning
confidence: 99%
“…Studies interested in the basal ablation of Antarctic ice islands have relied on deterioration estimates from satellite-borne altimetry data and surface ablation modelling (Jansen et al, 2007;Bouhier et al, 2017). Luckman et al (2010) modeled the thickness of Antarctic ice islands from remotely sensed altimetry data sourced from the Geoscience Laser Altimetry System onboard ICESat (the 'Ice, Cloud and land Elevation Satellite').…”
Section: Observing Ice Island Thinning With Remote Sensing and In-sitmentioning
confidence: 99%
“…Several examples validate the presence and accumulation of residual externalities. These include, amongst many others: the permanent and growing brown cloud in Asia (Ramanathan et al [16]); fragmentation of polar icebergs (Bouhier et al [17]); and the hole in the ozone layer (Fahey and Hegglin [18]). Hence, environmental economists deem that the definition of macroeconomic equilibrium should be revised to identify the disutility of residual externality (for example, see Thampapillai and Sinden [19]).…”
Section: Proposition 1: Residual Externalities Need To Be Factored Inmentioning
confidence: 99%